2007
DOI: 10.1016/j.jacc.2007.02.053
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value and Echocardiographic Determinants of Plasma Myeloperoxidase Levels in Chronic Heart Failure

Abstract: In chronic systolic HF, elevated plasma MPO levels are associated with an increased likelihood of more advanced HF. Moreover, elevated plasma MPO levels within a HF subject seem to be predictive of increased adverse clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
133
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(147 citation statements)
references
References 33 publications
9
133
2
3
Order By: Relevance
“…These results may in part support the findings that the expression and systemic levels of MPO are not elevated in stable CAD [27,28]. They are, however, in contrast to the suggestion to determine the systemic MPO levels as an emerging powerful and rapidly detectable marker for unstable CAD [24][25][26]. Our findings further support the concept that the robust release of MPO from activated PMN would reveal a state of acute inflammation in the coronary circulation preceding myocardial injury, but this may not be applied to other arterial disease.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These results may in part support the findings that the expression and systemic levels of MPO are not elevated in stable CAD [27,28]. They are, however, in contrast to the suggestion to determine the systemic MPO levels as an emerging powerful and rapidly detectable marker for unstable CAD [24][25][26]. Our findings further support the concept that the robust release of MPO from activated PMN would reveal a state of acute inflammation in the coronary circulation preceding myocardial injury, but this may not be applied to other arterial disease.…”
Section: Discussionsupporting
confidence: 74%
“…MPO has emerged as a powerful predictor for adverse outcome in patients with acute CAD [24][25][26]. Interestingly, Kubala et al [27] showed that the plasma levels of MPO were not elevated in patients with stable CAD, supporting the previous findings that the activation and recruitment of PMN was reduced in stable CAD [28].…”
Section: Discussionmentioning
confidence: 79%
“…MPO levels have been shown in multiple studies to track with incident risks of CVD events in subjects (53,(55)(56)(57). The present studies may help to explain prior reports of pro-inflammatory HDL in the acute phase setting, as well as during chronic inflammation such as in CVD.…”
Section: Discussionsupporting
confidence: 61%
“…This enzyme converts the low density lipoprotein into the atherogenic form, many reactive oxidants and free radicals occur and contribute to endothelial dysfunction by decreasing the nitric oxide level. MPO and MPO oxidant products can be a biomarker for the complications occurring during coronary heart disease and chronic heart failure (Tang et al, 2007;Morrow et al, 2008). Ronald et al (2009) determined that MPO activity is high in biochemical experiments comparing atherosclerotic plaques to normal arterial walls.…”
Section: Discussionmentioning
confidence: 99%